2017
DOI: 10.1515/bot-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Cell structure and microtubule organisation during gametogenesis of Ulva mutabilis Føyn (Chlorophyta)

Abstract: Cell structure and microtubule organisation during gametogenesis of the green alga Ulva mutabilis was studied using light microscopy, transmission electron microscopy (TEM) and tubulin immunofluorescence. Micro tubules in vegetative cells are organised in parallel bundles traversing the cortical cytoplasm. During gameto genesis, induced blade cells are transformed to gametangia, depending on the maturity of the algae and the removal of regulatory sporulation inhibitors. This differentiation is accompanied by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The microtubule cytoskeleton of somatic cells consists of parallel microtubule bundles arranged mainly in the cortical cytoplasm parallel to the plasmalemma. However, 36 h after induction, the microtubule bundles traverse the cortical cytoplasm converging on a particular area and then the microtubules starting from a pointed site at basal part of gametangium and forming a basket-like con guration with a circular opening at the top after 48 h [27]. Stratmann et al (1996) analyzed the DNA synthesis during gametogenesis and concluded that DNA replication starts from 25 hours after induction which is consistent with our RNA-seq data.…”
Section: Discussionsupporting
confidence: 84%
“…The microtubule cytoskeleton of somatic cells consists of parallel microtubule bundles arranged mainly in the cortical cytoplasm parallel to the plasmalemma. However, 36 h after induction, the microtubule bundles traverse the cortical cytoplasm converging on a particular area and then the microtubules starting from a pointed site at basal part of gametangium and forming a basket-like con guration with a circular opening at the top after 48 h [27]. Stratmann et al (1996) analyzed the DNA synthesis during gametogenesis and concluded that DNA replication starts from 25 hours after induction which is consistent with our RNA-seq data.…”
Section: Discussionsupporting
confidence: 84%
“…However, 36 h after induction, the microtubule bundles traverse the cortical cytoplasm converging on a particular area. Then, the microtubules start from a pointed site at the basal part of gametangium and form a basketlike configuration with a circular opening at the top after 48 h [27]. Stratmann et al [15] analyzed DNA synthesis during gametogenesis and concluded that DNA replication starts from 25 h after induction, which is consistent with our RNA-seq data.…”
Section: Dynamic Changes In Gene Regulation During Gametogenesissupporting
confidence: 86%
“…Genes related to DNA replication and microtubulebased movement were significantly upregulated after this irreversible timepoint. Electron microscope observations indeed demonstrate drastic rearrangements in microtubule morphology between 36 h and 48 h after induction [27]. The microtubule cytoskeleton of somatic cells consists of parallel microtubule bundles arranged mainly in the cortical cytoplasm parallel to the plasmalemma.…”
Section: Dynamic Changes In Gene Regulation During Gametogenesismentioning
confidence: 85%
“…The microtubule cytoskeleton of somatic cells consists of parallel microtubule bundles arranged mainly in the cortical cytoplasm parallel to the plasmalemma. However, 36 h after induction, the microtubule bundles traverse the cortical cytoplasm converging on a particular area and then the microtubules starting from a pointed site at basal part of gametangium and forming a basket-like configuration with a circular opening at the top after 48 h (Katsaros et al , 2017). Stratmann et al (1996) analyzed the DNA synthesis during gametogenesis and concluded that DNA replication starts from 25 hours after induction which is consistent with our RNA-seq data.…”
Section: Discussionmentioning
confidence: 99%